Underwater noise characteristics of offshore exploratory drilling and its impact on marine mammals - Huang, Long-Fei; Xu, Xiao-Mei; Yang, Liang-Liang; Huang, Shen-Qin; Zhang, Xin-Hai; Zhou, Yang-Liang (Frontiers in Marine Science, 2023)
Geotechnical survey is an important prerequisite to the construction of offshore wind farms. However, the impact of underwater survey noises has not yet been studied in details. In this paper, we studied transmission of underwater noises from offshore exploratory drilling (OED) at the Xiamen port. The noises were categorized into three types: hammering noises (hammering down of casings, which were 180-mm diameter steel pipes), vibrating noises (vibration of casings that had been hammered down), and drilling noises (generated during the borehole drilling process). We considered the variation in intensity of these three noise types, and set up two fixed and one movable stations to measure and analyze the source and propagation characteristics of these noises. The results indicate that hammering noise is an impulsive sound with a dominant frequency below 10 kHz, and source levels (SLs) of 197.1 dB re 1μPa @ 1 m (rms over 95% energy duration. 1–64,000 Hz) and 212.9 dB re 1μPa @ 1 m (peak). Vibrating and drilling noises are non-impulsive sounds with the fundamental frequencies of 41 Hz and 45 Hz, and SLs of 158.9 dB re 1μPa rms @ 1 m and 155.9 dB re 1μPa rms @ 1 m, respectively. The impact assessment of OED noises on five groups of marine mammals with different audible frequency ranges (Low (LF), High (HF), and Very High (VHF) frequency cetaceans, sirenians (SI), and phocid pinnipeds (PW)) demonstrates that hammering noise can induce a high risk of hearing damage to their hearing, at as far as 300 meters for VHF group, while drilling noise can only induce hearing damage at about 40 meters. Marine mammals are susceptible to behavior alteration, with a detectable distance of 1.9 km from the source, and it is recommended to set a warning zone with a radius of 1.9 km during OED construction.